1, 25(OH)2D3 inhibits oxidative stress and monocyte adhesion by mediating the upregulation of GCLC and GSH in endothelial cells treated with acetoacetate (ketosis). Issue 159 (May 2016) - Kanikarla-Marie, Preeti; Jain, Sushil K.
Highlights: 1, 25(OH)2 vitamin D inhibits ketone induced oxidative stress and monocyte adhesion in HUVEC. Beneficial effects of 1, 25(OH)2 vitamin D are impaired in cells that are deficient in glutathione. 1, 25(OH)2 vitamin D upregulates glutathione in a vitamin D receptor-dependent manner. Abstract: Background: There is a significantly higher incidence of cardiovascular disease (CVD) among type 1 diabetic (T1D) patients than among non-diabetic subjects. T1D is associated with hyperketonemia, a condition with elevated blood levels of ketones, in addition to hyperglycemia. The biochemical mechanism by which vitamin D (VD) may reduce the risk of CVD is not known. This study examines whether VD can be beneficial in reducing hyperketonemia (acetoacetate, AA) induced oxidative stress in endothelial cells. Methods: HUVEC were pretreated with 1, 25(OH)2 D3, and later exposed to the ketone body acetoacetate. Results: The increases in ROS production, ICAM-1 expression, MCP-1 secretion, and monocyte adhesion in HUVEC treated with AA were significantly reduced following treatment with 1, 25(OH)2 D3 . Interestingly, an increase in glutathione (GSH) levels was also observed with 1, 25(OH)2 D3 in ketone treated cells. The effects of 1, 25(OH)2 D3 on GSH, ROS, and monocyte-endothelial adhesion were prevented in GCLC knockdown HUVEC. This suggests that 1, 25(OH)2 D3 inhibits ROS, MCP-1, ICAM-1, and adherence of monocytes mediated by the upregulation of GCLC and GSH. Conclusion: This study provides evidence for the biochemical mechanism through which VD supplementation may reduce the excess monocyte adhesion to endothelium and inflammation associated with T1D.